IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 2 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN (KASUS PEMELIHARAAN PEJALAN KAKI JALAN SUDIRMAN) - Regian Lutfy; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The pedestrian facility is one of the points of the city's transport system, the pedestrian path is a space for activities to perform and functions as a circulation space for pedestrians that are separate from the circulation of other vehicles, whether motorized or not. This pedestrian path should provide comfort for the user of the pedestrian itself when crossing it. The purpose of this pedestrian facility is to ensure the level of human security in walking. With paved pedestrian facilities that have been provided by the government of course more convenient and provide a sense of security to users to walk in the middle of dense vehicles. But the fact that there is a lot of damage that occurs to pedestrian facilities is still less attention by the relevant government. Such as broken zebra cross, bridge crossing people and sidewalks. The maintenance of facilities should always be maintained by related parties in order to maintain the existing facilities and provide security and comfort for pedestrian users. The problem in this research is how the Implementation of Regional Regulation Policy of Pekanbaru City Number 2 year 2009 about Traffic and Road Transportation (Case of Peddling Pedestrian Street of Sudirman) and Factor - what factors that hinder the implementation of the policy. The purpose of this research is to know and analyze the Implementation of Regional Regulation Policy of Pekanbaru City Number 2 Year 2009 about Traffic and Road Transportation (Case of Peddling Pedestrian Street of Sudirman). The concept of theory that the author uses is policy and policy implementation. And the theory used is toeri according to Merile S. Grindle with two variables namely policy content and policy environment. This research uses qualitative research methods with descriptive data assessment. In data collection, the authors use interviews, observation and literature study. By using key information as a source of information.The results of this study indicate that the absence of maintenance that occurred in the field that is not in accordance with the pedestrian maintenance policy listed in the Regional Regulation of Pekanbaru City No. 2 of 2009 on Traffic and Road Transport. The inhibiting factors in policy implementation of Pekanbaru City Regulation No. 2 of 2009 on Traffic and Road Transport (Case of Maintenance of Jalan Sudirman Street Pedestrian) are Resources, Communication and Financial Budget to carry out pedestrian maintenance.Keywords: Implementation, Policy, maintenance, pedestrian